Reflection On Strategy Of Innovation - Hanipah, Hussin (2013)
An innovation mindset is an issued for all members in polytechnic’s academia now days. It is become a role and responsibility in every department in polytechnics since PSPTN Phase 11 launched. Head of department need to be actively involved in setting the mindset, direction, and environment for innovation. They also instill a confidence in their member of faculties.